Pengaruh Intensitas Paparan Konten TikTok Gaya Hidup Barat terhadap Perilaku Berpakaian Siswi Kelas IX MTsN 2 Padang - Wildan Hadi, Muhammad; Afdal; Dian Sari, Gusni; Meivilona Yendi, Frischa (Journal of Practice Learning and Educational Development, 2026)
The development of social media, especially TikTok, has brought about an increasingly massive wave of cultural globalization, including the dissemination of Western lifestyle content that is easily accessible to teenagers. This phenomenon has become a crucial issue in educational environments based on religious values, such as madrasahs, because it has the potential to influence the formation of students' identity, values, and dressing behavior. Conceptually, this research is based on the relationship between the intensity of digital media exposure, the internalization of Western popular cultural values, and changes in adolescent social behavior in the context of dress norms in Islamic-based schools. This study aims to analyze the influence of the intensity of exposure to Western lifestyle TikTok content on the dressing behavior of ninth-grade female students at MTsN 2 Padang. This research uses a quantitative approach with a survey method. The research sample consists of ninth-grade female students from MTsN 2 Padang, selected using the proportional random sampling technique. Data were collected thru a closed questionnaire that had been tested for validity and reliability, and then analyzed using simple linear regression analysis. The research results show that the intensity of exposure to Western lifestyle TikTok content significantly affects the students' dressing behavior, both in terms of clothing model preferences, dressing outside of school, and the tendency to imitate social media influencer figures. These findings indicate that the higher the intensity of exposure to such content, the greater the tendency for a shift in dressing behavior that is less aligned with the dress norms of the madrasah.